In vitro evaluation of six chemical agents on smooth Brucella melitensis strain - Wang, Zhen (Ann Clin Microbiol Antimicrob, 2015)
Brucellosis is a zoonosis that disseminated by a variety of ways between animals and humans. The effective disinfection of contaminated environments, soil, feces, and animal bodies plays an irreplaceable role in the prevention and control of brucellosis. To kill Brucella effectively, the bactericidal effects of frequently used disinfectants (including aldehydes, halogens, quaternary ammonium compound, phenolics, and alkalines) and the potential factors that influence disinfection effects were determined in the present study. The results revealed that the minimum bactericidal concentrations (MBCs) of the six disinfectants were all significantly lower than the routinely used concentrations, and all the tested disinfectants were effective against B. melitensis NI. The results of quantitative determination showed that the bactericidal effects of the disinfectants were influenced by their concentration, exposure time, dirty condition and the temperature. Under dirty conditions and a low temperatures, sodium hypochlorite and sodium hydroxide showed better bactericidal effect, while benzalkonium chloride was almost without bactericidal ability. In addition, increasing the disinfectant concentration at low temperatures can improve the bactericidal effect. The present study suggested that Brucella is sensitive to commonly used disinfectants. However, the bactericidal effect is vulnerable to dirty conditions and low temperatures. Thus, it is necessary to test the in vitro sensitivity of disinfectants that are commonly used on farms or the new disinfectant formulations periodically, with the aim of improving the efficacy of animal and human brucellosis prevention programs.